A design of broadband bandpass frequency selective surface. Issue 9 (27th May 2022) - Li, Meiling; Hong, Mudan; Yang, Qihao; Zheng, Qi; Yang, Xuexia; Yi, Zixuan
Abstract: In this paper, a broadband frequency selective surface (FSS) based on a multilayer coupling cascade is presented. The overall structure consists of three metallic layers and two dielectric substrates. In addition, a crosspatch terminated with an E‐shaped structure and a gradient cross structure with a slot is introduced in the middle metallic layer to control the transmission zero and extent of the current path, respectively. The unit cell periodicity is about 0.27 λ 0 ${λ }_{0}$, and the overall thickness of the dielectric layer is about 0.087 λ 0 ${λ }_{0}$ . Prototypes of the proposed FSS are designed and simulated, and an equivalent circuit model is developed to explain the mechanism further. Finally, the FSS prototype works at the center frequency of 12.2 GHz with a relative −0.5 dB bandwidth of 70% and a relative −3dB bandwidth of 104%. The frequency responses are relatively stable with the variation of incidence angles from 0° to 60°.